Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Crusciol, Carlos A. C. [UNESP]; Marques, Rubia R. [UNESP]; Carmeis Filho, Antonio C. A. [UNESP]; Soratto, Rogério P. [UNESP]; Costa, Claudio H. M.; Ferrari Neto, Jayme [UNESP]; Castro, Gustavo S. A.; Pariz, Cristiano M. [UNESP]; Castilhos, André M. [UNESP]; Franzluebbers, Alan J. (Springer Nature, 2019)
In tropical integrated crop-livestock under no-till (NT) systems, the surface application/reapplication of lime and/or gypsum can reduce re-acidification rate of the soil and improve plant nutrition, crop yields, and profitability. This study was conducted in the Brazilian Cerrado, which has dry winters, and aimed to evaluate the effects of surface application/reapplication of lime and/or gypsum on soil improvement, plant nutrition and crop yield improvement, as well as the forage dry matter (DM) yield, estimated meat production, and economic results. The crop rotation used between November 2004 and August 2008 was as follows: peanut (Arachis hypogaea) and white oat (Avena sativa) cultivated alone (on the first and second spring/summer and autumn/winter, respectively) and corn (Zea mays) intercropped with palisade grass [Urochloa brizantha cv. ‘Marandu’] and pasture (on the third and fourth spring/summer and autumn/winter, respectively). The experimental design was a randomized block with four replications. The treatments consisted of natural conditions of a sandy clay loam kaolinitic and thermic Typic Haplorthox (control) and the surface application of lime and/or gypsum in October 2002 and reapplication in November 2004. Surface liming was an efficient practice for increasing pH and reducing the exchangeable acidity (H + Al) and concentration of Al extending to a depth of 0.60 m. Gypsum application increased Ca2+ levels through the soil profile. Liming (with or without gypsum) had a positive effect on the nutrient acquisition by peanut, white oat, and corn crops, producing on average 48%, 52%, and 61% more pod and grain yield, respectively, than that obtained in the absence of soil amendments and with gypsum alone. The surface application of lime + gypsum also promoted forage DM yield of corn-palisade grass intercropping 22% higher than lime application and 164% higher than control; estimated meat production 26% higher than lime application and 225% higher than control, and increased economic results during four growing seasons. The surface application of lime + gypsum is an essential tool for food production in NT tropical agriculture with high soil acidity.
Keywords: Grain yield; Integrated crop-livestock system; Profitability; Soil acidity; Soil amendment